2019
DOI: 10.4269/ajtmh.18-0434
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Central Nervous System Infections in a Rural Area of Nepal Using Molecular Approaches

Abstract: The etiology of infections of the central nervous system (CNS) in Nepal often remains unrecognized because of underdeveloped laboratory facilities. The aim of this study was to investigate the etiology of CNS infections in a rural area of Nepal using molecular methods. From November 2014 to February 2016, cerebrospinal fluid (CSF) was collected from 176 consecutive patients presenting at United Mission Hospital in Tansen, Nepal, with symptoms of possible CNS infection. After the CSF samples were stored and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…The MeningoFinder 2SMART (PathoFinder, Maastricht, the Netherlands), available for research use only, detects nine bacteria, twelve viruses and two fungi, has been compared with the Fil-mArray® ME panel in one study and was shown to be less sensitive for EV and Cryptococcus [31].…”
Section: Multiplex Pcr Panels: Analytical and Clinical Performancesmentioning
confidence: 99%
See 1 more Smart Citation
“…The MeningoFinder 2SMART (PathoFinder, Maastricht, the Netherlands), available for research use only, detects nine bacteria, twelve viruses and two fungi, has been compared with the Fil-mArray® ME panel in one study and was shown to be less sensitive for EV and Cryptococcus [31].…”
Section: Multiplex Pcr Panels: Analytical and Clinical Performancesmentioning
confidence: 99%
“…In resource-limited settings, where the expertise required to perform more labour-intensive molecular tests is often lacking, easyto-use multiplex PCR panels can improve CNS infection diagnostics [31,50,51], although the impact on antimicrobial use and management might be lower in this context [50]. Pulmonary tuberculosis diagnosis has been improved by the use of such a tool [52].…”
Section: Qualitative Versus Quantitative Assaysmentioning
confidence: 99%
“…These two agents were not detected together in any patient. The rate of detection of HHV-6 in the CSF of children is reported in the range of 0.3-32% in the presence of sepsis, seizures, and neurological findings with fever and in the range of 3.3-4.2% in the presence of meningitis [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. HHV-7 is a rare aetiological agent in CNS infections in children, the rate of detection in CSF varies between 1% and 14.8%, and its incidence increases especially with increasing age [11,12,16,22,[25][26][27][28][29][30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the detection of HHV-7 in 3 children older than the others brings to mind that HHV-7 reactivation may have developed in these children. It has been reported in the literature that reactivation of HHV-7 is seen rather than primary infection in adults [11,12,16,22,[24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation